2013
DOI: 10.1089/cap.2013.0054
|View full text |Cite
|
Sign up to set email alerts
|

Atomoxetine Improved Attention in Children and Adolescents with Attention-Deficit/Hyperactivity Disorder and Dyslexia in a 16 Week, Acute, Randomized, Double-Blind Trial

Abstract: Objective: The purpose of this study was to evaluate atomoxetine treatment effects in attention-deficit/hyperactivity disorder (ADHD-only), attention-deficit/hyperactivity disorder with comorbid dyslexia (ADHD + D), or dyslexia only on ADHD core symptoms and on sluggish cognitive tempo (SCT), working memory, life performance, and self-concept. Methods: Children and adolescents (10-16 years of age) with ADHD + D (n = 124), dyslexia-only (n = 58), or ADHDonly (n = 27) received atomoxetine (1.0-1.4 mg/kg/day) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 31 publications
4
46
0
2
Order By: Relevance
“…An evaluation of this intervention did show a reduction in SCT symptoms among children diagnosed with ADHD-I 77 . The only study evaluating the effects of medication on SCT symptoms found atomoxetine to reduce SCT symptoms in youth with ADHD 78 , which aligns with other studies showing atomoxetine to be effective for youth with ADHD who have co-occurring internalizing problems (though findings are stronger for comorbid anxiety than for comorbid depression) 7981 . The sole study evaluating SCT as a predictor of treatment response did not find SCT to impact response to methylphenidate 44 , although it should be acknowledged that this study used a limited measure of SCT and did not use a randomized design.…”
Section: Discussionsupporting
confidence: 74%
“…An evaluation of this intervention did show a reduction in SCT symptoms among children diagnosed with ADHD-I 77 . The only study evaluating the effects of medication on SCT symptoms found atomoxetine to reduce SCT symptoms in youth with ADHD 78 , which aligns with other studies showing atomoxetine to be effective for youth with ADHD who have co-occurring internalizing problems (though findings are stronger for comorbid anxiety than for comorbid depression) 7981 . The sole study evaluating SCT as a predictor of treatment response did not find SCT to impact response to methylphenidate 44 , although it should be acknowledged that this study used a limited measure of SCT and did not use a randomized design.…”
Section: Discussionsupporting
confidence: 74%
“…The pediatric population also included patients with comorbid conditions of tics, depression, anxiety, oppositional defiant disorder (ODD), reading disorder, autism spectrum disorder, and dyslexia Bangs et al 2007;Geller et al 2007;Bangs et al 2008a;de Jong et al 2009;Dell'agnello et al 2009;Dittmann et al 2011;Harfterkamp et al 2012;Wietecha et al 2013). The adult population included patients with comorbid social anxiety and alcohol use disorders (Wilens et al 2008;Adler et al 2009a).…”
Section: Methodsmentioning
confidence: 99%
“…Each clinical trial included in the analysis had institutional review board (IRB) approval (study level and site level) and was conducted in accordance with the Declaration of Helsinki. All adult patients and a parent or guardian for each minor patient provided written informed consent to participate (Michelson et al 2001(Michelson et al , 2002Spencer et al 2002;Michelson et al 2003;Kelsey et al 2004;Allen et al 2005;Weiss et al 2005;Bangs et al 2007;Gau et al 2007;Geller et al 2007;Adler et al 2008;Bangs et al 2008a;Newcorn et al 2008;Wilens et al 2008;Adler et al 2009a,b;Block et al 2009;de Jong et al 2009;Dell'agnello et al 2009;Montoya et al 2009;Svanborg et al 2009;Takahashi et al 2009;Martenyi et al 2010;Dittmann et al 2011;Young et al 2011;Harfterkamp et al 2012;Hirata et al 2012;Wehmeier et al 2012;Durell et al 2013;Wietecha et al 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Resultado semelhante foi encontrado na pesquisa realizada por Wietecha et al (2013), em que crianças com TDAH, com DD e com DD+TDAH tiveram seu desempenho em escalas de comportamento e em tarefa de memória operacional avaliadas antes e depois de serem submetidas a tratamento com atomoxetina, sendo verificada a melhora dos sintomas de TDAH nas crianças com DD+TDAH e com TDAH, mas não com as crianças só com DD, indicando que o medicamento atua de forma específica nas questões atencionais e comportamentais.…”
Section: Correlação Entre As Variáveis Pesquisadasunclassified